ANALISA PENERAPAN PENCATATAN AKUNTANSI DAN DAMPAKNYA TERHADAP KEBERLANGSUNGAN UMKM PADA TOKO SOLIHIN AKSESORIS DAN PALEN DI DESA AJUNG - Lailatul Qomariah (Jurnal Studi Akuntansi Pajak Keuangan, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy, especially in absorbing labor and supporting income equality. Based on the latest data report from the Ministry of Cooperatives and SMEs in 2024, there are around 65 million MSME units in Indonesia which contribute around 60% to the national Gross Domestic Product (GDP). This figure shows the large contribution of MSMEs in boosting national economic growth. In this study, the author used a qualitative method with a case study plan to analyze accounting recording practices and their impact on the sustainability of MSMEs in Ajung Village. This approach was chosen in order to comprehensively understand the experiences and perceptions of business actors regarding financial recording. The results of the study revealed that MSMEs in the area had not implemented a structured recording system and business owners had limited understanding of accounting recording. Therefore, it is recommended that MSME owners start adopting routine and simple financial recording, and increase basic accounting knowledge through training or easily accessible learning resources to support their business desires.